Antimicrobial Resistance: Mechanisms, Screening Techniques and Biosensors (Journal of Pharmaceutical Negative Results, 2022)
Antimicrobial resistance is one of the greatest dangers to public health on a worldwide scale. Even though the evolution of resistant microbes is a naturally occurring phenomenon, the excessive or improper use of antimicrobial agents has significantly impacted resistance evolution. Effective treatment techniques can be guided by rapid diagnostic tests of these resistance to detect drug-resistant microorganisms quickly, assess antimicrobial susceptibility, and bacterial infections from differentiate viral. In addition, quick diagnostic test could assist epidemiological surveillance by monitoring developing resistance to pathogenic pathogens and their transmission. Methods for AMR detection, and surveillance, includes Microscopy, PCR, DNA microarray, matrix-assisted laser desorption,Pyrosequencing, NAAT, whole genome sequencing, Immuno detection, spectroscopy, FTIR, Biosensor, and microfluidics technology. The AMR turmoil necessitates a concerted effort from researchers to improve the current approaches for treatment and diagnosis by developing novel techniques that circumvent the limitations and drawbacks of the best alternatives and conventional AST methods. This review mainly summarizes the different emerging diagnostic techniques used to detect antibiotic resistance and the mechanism of drug resistance. These emerging diagnostic strategies might improve medication development strategies and the surveillance of resistance evolution.